Research collaboration with Halfen Moment Sdn. Bhd. / Ir. Mohd Asha'ari Masrom - Masrom, Mohd Asha'ari (Unit Penerbitan FKAPP, 2019)
This collaboration initiated from a research project funded by the Ministry of Higher Education under the Fundamental Research Grant Scheme for three years duration. The research is about the innovative connection between precast rocking wall and precast floor in the load bearing structure. The precast connections are tested in the heavy structural laboratory to evaluate the performance of connection under seismic loading. In this respect, Mr Gary Connah (Technical and Development Manager) and Mr KC Toh (Technical Manager) from Halfen Moment Sdn. Bhd. were interested in collaborating in the research project by supplying their precast products and contribute their expertise for the project successfulness. This collaboration has exhibited a good practice of industrial linkage, which in line against the government's call for greater cooperation between universities and industry.